2015
DOI: 10.1161/atvbaha.115.305445
|View full text |Cite
|
Sign up to set email alerts
|

Rare SNP rs12731181 in the miR-590-3p Target Site of the Prostaglandin F Receptor Gene Confers Risk for Essential Hypertension in the Han Chinese Population

Abstract: P rostanoids are biologically active derivatives of arachidonic acid that is released from membrane phospholipids and then converted through cyclooxygenase metabolism. These lipid mediators play an important role in blood pressure (BP) homeostasis. Both traditional nonsteroidal anti-inflammatory drugs and cyclooxygenase-2 selective nonsteroidal antiinflammatory drugs can elevate BP in patients. 1 Vasodilator prostanoids, such as prostaglandin (PG) I 2 and PGE 2 , are essential for regulating renal blood flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
18
2
Order By: Relevance
“…These miRs are all important regulators of VSMC phenotype plasticity. A further study in a Chinese population identified the SNP rs12731181 (A to G) in the prostaglandin F 2 α receptor that was more prevalent in hypertensive individuals ( Xiao et al, 2015 ). This polymorphism reduces the likelihood of miR-590-3p binding, thus increasing prostaglandin F 2 α receptor expression and enhancing prostaglandin-mediated contractility of VSMCs ( Xiao et al, 2015 ).…”
Section: Regulation Of Vascular Smooth Muscle Cell Function By Ementioning
confidence: 99%
“…These miRs are all important regulators of VSMC phenotype plasticity. A further study in a Chinese population identified the SNP rs12731181 (A to G) in the prostaglandin F 2 α receptor that was more prevalent in hypertensive individuals ( Xiao et al, 2015 ). This polymorphism reduces the likelihood of miR-590-3p binding, thus increasing prostaglandin F 2 α receptor expression and enhancing prostaglandin-mediated contractility of VSMCs ( Xiao et al, 2015 ).…”
Section: Regulation Of Vascular Smooth Muscle Cell Function By Ementioning
confidence: 99%
“…Human FP (hFP) hepatocyte transgenic (HCTG) and nontransgenic (NTG) littermates were obtained from the mating of Tg-hFP-STOP Flox (16) and Alb Cre mice. FP exon2-floxed mice (FP F/F ) were generated through CRISPR/Cas9 technology by Shanghai Biomodel Organism Science & Technology Development Co., Ltd. (Shanghai, People's Republic of China) and crossed with Alb Cre mice to obtain hepatic FP-deficient mice (FP F/F Alb cre ).…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Other genes showing significant post-transcriptional regulation were the following: The sterile α motif domain containing 4A ( SAMD4A ) that has been linked to the inhibition of preadipocyte differentiation and leanness phenotype in knockdown experiments [84,85]. The prostaglandin F2-receptor protein (PTGFR), for which overexpression has been associated with hypertension and obesity risk [86], and its repression appears to improve insulin sensitivity and glucose homeostasis [87]. The expression of serpin E1 and E2 ( SERPINE1 , SERPINE2 ) is linked to obesogenic states and diabetic symptoms [88], while their inhibition improved glucose metabolism [89].…”
Section: Discussionmentioning
confidence: 99%